Integrated Phytochemical and Hematological Assessment of Hydroethanolic Leaf Extract of Justicia carnea in Streptozotocin-Induced Diabetic Wistar Rats - Ojeaburu, Samuel Ifidon; Uanseoje, Sylvester Obaika (Journal of Science Research and Reviews, 2025)
Diabetes mellitus, a multifactorial metabolic disorder, is often associated with hematological and oxidative alterations that contribute to disease complications. This study investigated the phytochemical composition and biochemical effects of the hydroethanolic leaf extract of Justicia carnea on hematological parameters in streptozotocin-induced diabetic Wistar rats. Thirty-six (36) male albino Wistar rats were divided into six groups (n = 6). Diabetes was induced by a single intraperitoneal injection of streptozotocin (50 mg/kg), except in the normal control group. The diabetic control group received no treatment, while the reference group received metformin (50 mg/kg). Test groups were orally administered Justicia carnea hydroethanolic extract at doses of 100, 200, and 500 mg/kg daily for 28 days. Acute toxicity was assessed using Lorke’s method. At the end of the experiment, fasting blood glucose levels were measured, and blood samples were collected via cardiac puncture for hematological analysis. Phytochemical screening revealed the presence of flavonoids, phenols, steroids, tannins, and terpenoids, indicating significant bioactive potential. Proximate analysis showed high carbohydrate (50.91 %) and moisture (21.11 %) content, with lower levels of crude fat (0.25 %) and protein (1.25 %). Treatment with Justicia carnea extract produced a dose-dependent improvement in hematological indices, including red blood cell count, hemoglobin concentration, and white blood cells, compared with diabetic controls. These effects suggest a restorative influence on hematopoietic function, potentially mediated by phytochemical constituents with antioxidant or cytoprotective activity. These findings suggest that Justicia carnea may possess hematoprotective and restorative properties beneficial in the management of diabetes-induced hematological alterations.